Development of Under Bridge Crossing Navigation for Autonomous Vessel - Uzair, Muhamad Kamal Hazim (Universiti Teknologi PETRONAS, 2021)
In enhancing the technology of autonomous vessel, the application of GPS navigation is being continuously develop in this area of study to improve the efficiency of autopilot and unmanned vessel in such way it will optimize the motion of vessel from point A to point B as well as promote the overhead cost reduction with the help of ‘auto-pilot’ or unmanned vessel. Several limitations of current technology of autonomous vessel have been pinpointed and the focus of this project is to encounter the situation by developing the extra features to it. In accordance to a study by Allianz, 75% and 96% of maritime accidents are caused due to human error [1]. Autonomous vessel has its role to reduce the reliance towards man-control that obviously can pose mistakes that might possibly cause accidents due to fatigue and bad judgment [2]. The quantity of crew on a ship/vessel can be reduced and it will pose auxiliary cost reduction such as onboard provisions and insurance cost as mentioned earlier.